Diagnostic endoscopic ultrasound: is it a reliable investigation - De zoysa, M.I.M.; Sivaganesh, S.; Samarasekera, D.N. (My University, 2012)
Endoscopic ultrasound (endosonography) is fast becoming the gold standard in the diagnosis of benign lesions and staging of malignant lesions of the gastrointestinal (GI) tract. We analyzed the results of diagnostic endosonography carried out in our GI physiology laboratory and compared the findings with conventional external ultrasound scanning and/or CT.